Cats in the zoo - Smith, Roland; Munoz, William, Photographer (Brookfield, Conn. Millbrook Press, 1994)
Describes the habits of cats in the wild as well as the care cats receive in today's zoo in order to prevent their extinction.
Includes bibliographical references and index
68524
Keywords: Felidae -- Juvenile literature; Zoo animals -- Juvenile literature; Felidae; Cats. -- Felines; Zoo animals